Moving Events in Time: Time-Referent Hand-Arm Movements Influence Perceived Temporal Distance to Past Events. - Blom, Stephanie S. A. H.; Semin, Gün R. (Journal of Experimental Psychology. General, 2013)
We examine and find support for the hypothesis that time-referent hand-arm movements influence temporal judgments. In line with the concept of "left is associated with earlier times, and right is associated with later times," we show that performing left (right) hand-arm movements while thinking about a past event increases (decreases) the perceived temporal distance to the event. These findings show for the first time that hand-arm movements can influence the perceived temporal distance to events.